Potensi dan Pengembangan Virtual Tour sebagai Alternatif Wisata di Kintamani dan Gianyar - Lumanauw, Nelsye (Innovative: Journal Of Social Science Research, 2024)
The development of virtual tours in the Kintamani and Gianyar areas was crucial as a promotional tool for tourism destinations by leveraging the increasingly strong digitalization trend. The natural and cultural potentials in these areas could become attractive content for virtual tourists. This research used qualitative methods, including in-depth interviews and document analysis, to identify key factors in the development of virtual tours, such as the availability of technology, skilled human resources, and integration strategies for physical promotion. The results showed that with adequate technology and skilled human resources, virtual tours could serve as an alternative form of tourism, providing unique experiences and aligning with the developments of the digital era. Future research recommendations included analyzing the effectiveness of virtual tours, the impact of new technologies, and collaboration strategies among stakeholders to maximize the potential of virtual tours in Kintamani and Gianyar.